THE RELATION BETWEEN MAXIMUM RATE OF PHOTOSYNTHESIS AND CONCENTRATION OF CHLOROPHYLL - Emerson, Robert (The Rockefeller University Press, 1929)
Willstätter and Stoll have studied the rate of photosynthesis as a function of chlorophyll content. However, their experiments fail to reveal any regular relationship between these two quantities, probably because, in order to obtain material differing widely in chlorophyll content, they were obliged to use leaves which were not comparable in other respects. The writer describes a method for varying the chlorophyll content per unit volume of cells of Chlorella vulgaris, maintaining other factors constant. Experiments are described which show that the maximum rate of photosynthesis is a smooth function of the chlorophyll content.